The ethics of bioethics conferencing in Qatar - Jecker, Nancy (Bioethics, 2023)
In 2022, the International Association of Bioethics (IAB) announced that the 17th World Congress of Bioethics would be held in Doha, Qatar. In response to ethical concerns expressed about the Qatar selection, the IAB Board of Directors developed and posted to the IAB website a response using a Q&A format. In this Letter, we (the IAB President and Vice President) address concerns about the ethics of bioethics conferencing raised in a 2023 Letter to the Editor of Bioethics by Van der Graaf et al. We do not represent the Board of Directors, and this Letter expresses solely our own views.